Livelihoods in Dilapidated Neighborhoods of Jimma City The Efforts of Poor Urban Dwellers to Survive (Global Journal of Human-Social Science, 2018)
This study is entitled as livelihoods in dilapidated neighborhoods of Jimma City The efforts of poor urban dwellers to survive in the city of Jimma To study it variety of objectives was emanated from the general objective of the study The general objective of this study is to investigate the life making of the poor in dilapidated neighborhoods Four specific objectives were derived from the general objective These specific objectives include describing the nature of vulnerability dwellers face in the study area identifying the major types of livelihood strategies the poor use in the study area examining assets of the of the households and the access to these assets and to describe the outcomes of their livelihood To address these objectives qualitative and quantitative research methods were used A cross-sectional survey was conducted on 50 respondents purposively sampled from the Hirmata Kebele In-depth interviews were also conducted with seven informants One focus group discussion was also conducted to get both in-depth information on the issue at hand Secondary data was also used Therefore the study reveals that households in the study area face variety of vulnerabilities Majority of the respondents in the study site characterized by low socioeconomic status low income and concerning the educational status more than 60 of the respondents were at primary and below primary level Significant amount of respondents were unemployed 28 and engaged in fragile self-employed activities 52 This result is also supported by data collected via qualitative data collection instruments Majority of the subjects of the study were participating in survival livelihoods mainly such as street vending 85 fishing and domestic service The available assets at hand were fragile that do not allow them lead a secured and sustainable livelihood Support in the form of financial aid loan credit from government and other concerned bodies are recommend
Keywords: livelihood; urban poor; dilapidated neighborhood; assets; urban; coping strategy